Performance analysis of FIS wc-races (SL, GS) from season 2011-2012 - 2015-2016 concerning course setting and slope characteristics - Huber, A.; Spitzenpfeil, P.; Waibel, K.; Doppelhofer, A. (Science and Skiing VII, 2018)
Because having information about the course is essential for every ski racer, almost all coaches try to provide data concerning gate distances, the characteristics of course setting, and the slope conditions (e.g., icy, bumpy). Usually this information is not shared with other teams. Published data is only available from one study with the data of seven races (Gilgien et al., 2015). The aim of this study is to explore changes in these characteristics during the last five years and any existing relationships between the characteristics.